Price Pass-Through and the Minimum Wage - Aaronson, Daniel (The Review of Economics and Statistics, 2001)
This paper tests a textbook consequence of competitive markets: that an industry-wide increase in the price of labor is passed on to consumers through an increase in prices. Using several data sources on restaurant prices, I explore the price impact of minimum-wage hikes in Canada and the United States. Particular attention is paid to the timing of these price responses to gauge the ‘stickiness’ of minimum-wage cost shocks. I find that restaurant prices generally rise with changes in the wage bill and that this response is concentrated in the quarter surrounding the month during which the legislation is enacted.